The Influence of Islamic Social Finance Perception (Zakat, Infaq, Shadaqah) on Poverty Alleviation: A Study of ZIS Fund Recipients in Kuala Tungkal - Sri Kasnelly; Nurlaila Permata Sari (Universitas Muhammadiyah Purwokerto, 2026)
This study investigates the influence of public perception of Islamic Social Finance (ISF), with particular focus on Zakat, Infaq, and Shadaqah (ZIS), on poverty alleviation efforts in the Kuala Tungkal region. Employing a quantitative approach through explanatory research design, data were collected from 51 individuals who had received ZIS assistance. Analysis using simple linear regression revealed a positive and statistically significant correlation between public perception of ZIS and the success of poverty alleviation programs. The findings were validated by a significance value of 0.000, which falls below the 0.05 threshold, and a t-value of 5.817, which exceeds the critical t-table value of 2.00404. The resulting regression equation, Y = 0.927 + 0.775X, with a Beta coefficient of 0.624, indicates that each one-unit increase in ZIS perception contributes to a 0.775-unit improvement in poverty alleviation effectiveness. This study confirms that the level of community understanding and positive attitudes toward ZIS plays a crucial role in maximizing its potential as an instrument for reducing poverty in Kuala Tungkal